The Correlation Between the Persistence of Methicillin Resistant Staphylococcus Aureus Isolates to Mupirocine and Toxin-Antitoxin Type II Genes - Al-Hadban, Wedean; Ali, Maysaa Adil; Kandala, Nuha (Iraqi Journal of Science, 2022)
Under high concentrations of antibiotics, a fraction of the bacterial population exhibits a phenomenon known as persistence. Toxin- system (TA system) has been reported to be involved in the formation of E. coli, Mycobacterium, and S. aureus persisters.  In this study, the ability of thirty Iraqi isolates of MRSA to form in vitro persister cells after exposure to three different antibiotics (Ceftriaxone 30 µg, Mecillinam 10 µg, and Mupirocin 20 µg) was examined by TD test. Additionally, efflux pump inhibitor [Fluphenazine 0.25 mg/ml] was combined with the antibiotic that triggered persister formation. The distribution of mazEF and yefM-yoeB (Type II TA system) in the tested isolates was detected by PCR. 91% of Mupirocin susceptible isolates formed persister cells.42% of the persistent level was reduced when Mupirocin was combined with the Fluphenazine. Genes for homologs of the yefM-yoeB and mazEF TA system were present in 100% of the tested isolates. The prevalence of these genes in the tested isolates suggested a link between persistence and the TA system. Further investigation is required to study the expression of these genes under stress conditions.